Pengaruh Kualitas Pelayanan, Keragaman Produk dan Harga Terhadap Kepuasan Konsumen Pada Kedai Mutia Jl. A. Yani, Kec. Kertosono, Kab. Nganjuk, Jawa Timur - farida, eka nur; Dra. Diana Juni Mulyati, MM, Drs. Agung Pujianto, MM (Research Journal of Social Science and Economics, 2025)
Kedai Mutia is a coffee shop in Kertosono, Nganjuk, East Java, which is still a lot of visitors. Kertosono is one of the districts in Nganjuk Regency which is quite busy. Entrepreneurs must use the right strategy to satisfy consumers, namely with quality service, a variety of distinctive and varied products and appropriate and affordable prices so that the products offered are different from other competitors. The formulation of the problem in this study is whether there is an influence of service quality, product diversity, and price on consumer satisfaction at Mutia Store JL. A. Yani. Kertosono District, Nganjuk, East Java. With the aim of research is to know and analyze to determine the effect of Service Quality, Product Diversity, and Prices on Consumer Satisfaction, customers of Kedai Mutia. This type of research uses quantitative methods with correlation research types with d lata collection techniques using questionnaires. The population in this study were consumers who had visited Kedai Mutia with a sample of 96 respondents. The analytical method used in this study is multiple regression analysis, validity and reliability tests, classic assumption test which consists of, linearity test, normality test, multicollinearity test, heteroscedasticity test, and hypothesis testing which consists of t test, determination test, test r with the help of the IBM SPSS version 20 for windows program. The results of this study indicate that the variable Service Quality has a positive and significant effect on the variable of Consumer Satisfaction of Mutia Shop, then the variable of Product Diversity has a positive and significant effect on Consumer Satisfaction of Mutia Shop, then the price variable has a positive and significant effect on Customer Satisfaction of Mutia Kertosono Shop. Keywords: Service Quality, Product Diversity, Price, Consumer Satisfaction.